Electronic money and mobile payments: the transformation of credit services ("Journal "U". Economy. Management. Finance.", 2025)
The research is aimed at studying the process of transformation of credit services under the influence of the introduction of electronic money and mobile payments. Modern technological changes that accelerate the pace of transition to digital financing methods and contribute to increasing the availability of credit products are considered. The advantages and potential problems arising in connection with the development of electronic lending and changing consumer preferences are shown.
Keywords: electronic money; mobile payments; lending; non-cash payments